Description of a new mite pest (Acari: Eriophyoidea) infesting Azadirachta indica from India. - Sarkar, Sanjay (International Journal of Agriculture System, 2024)
Among the Acari, eriophyoid mite is considered as an important pest as they produce various damage symptoms while feeding on plants. During the general surveys for eriophyoid mites from present study area a new species, Caleptrimerus neemivorus sp. nov. of the family Eriophyidae was found along the margin gall of the leaves of Azadirachta indica A. Juss. (Meliaceae). This new phytophagous mite species was described and illustrated from the specimens collected at English bazar, Malda (25Â° 0' 39.0276'' N and 88Â° 8' 27.9528'' E.), West Bengal, India. Relationships of new species with other eriophyoid species are also provided. After proper diagnosis of the species it is found that this is the fourth eriohyoid mite species described from Azadirachta indica in India. This new species is a gall forming plant mite and causes damage to this economically important medicinal plant. For proper control of the mite pest, the taxonomic study of this mite and their relation to the host plant is very much essential.